In In Between Spaces: Ruang Fisik-Emosi dalam Pencapaian Tujuan PAK Menurut Karen Tye dan Thomas Groome - Nimali Fidelis Buke; Mariska Lauterboom; Gilbet Tahirim B.P. Simanullang (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2026)
This study aims to analyze the role of physical space and emotional space in achieving the theological goals of Christian Religious Education. The method used in this research is qualitative with a descriptive research design and library research as the data collection technique. Unlike previous studies, this research specifically employs library-based data collection as its primary method. This study draws on the theory of Karen B. Tye and the concept of Christian Religious Education, as outlined by Thomas H. Groome. Physical space refers to all physical forms that can be observed, touched, measured, and directly perceived by the senses. Meanwhile, emotional space refers to attitudes of acceptance, openness, and a sense of security within the learning process. Both physical space and emotional space play an important role in achieving the theological goals of Christian Religious Education, particularly in the process of socializing Christian faith values.